Concomitant Substance Use Increases the Toxic Effect of synthetic cannabinoid (Bonsai): A Prospective Study: Toxic Effect of Bonsai - Beydilli, İnan and DUYAN, Murat and Yılmaz, Fevzi and Arslan, Engin Deniz and Korkmaz, İlhan and Akçimen, Mehmet and Keşaplı, Mustafa and İmak, Arefe and Çakır, Umut Cengiz and Kavalcı, Cemil and Ararat, Ertan and Ellidağ, Hamit (Acta Biomedica Atenei Parmensis, 2020)
Objective: In this study, we aimed to contribute to the literature by evaluating bonsai and additional drugs. Materials and Methods: This prospective study was conducted on 217 patients who admitted to the emergency department (ED) with bonsai intake between December 20, 2014 and January 1, 2016, according to the patient history obtained from the patients. While 168 patients with negative urinary metabolites results were excluded from the study, 49 patients with positive urinary metabolites were included in the study. Patients were divided into two groups. The first group consisted of patients with only bonsai intake and the second group consisted of patients with bonsai and concomitant drug intake. The groups were compared in terms of symptoms, findings, blood gas values, duration of the symptoms, discharge time, hospitalization, and mortality rate. Data were analyzed using the Chi-square, the Fisher’s exacttest, the Student t-test, and the Mann-Whitney U test. Data were evaluated at the 95% confidence interval. P<0.05 was considered statistically significant. Results: The mean age of 49 patients included in the study was 26.7±8.9 years and 91.8% (n=45) of the patients were male. Concomittant drug intake was identified in 69.4% of patients. Concomitant drug use was as follows: cocaine (20.4%, n=10), amphetamines (14.3%, n=7), methamphetamines (8,2%, n=4,) tetrahydrocannabinol (32.7%, n=16), opiates (18.4%, n=9) and alcohol (30.6%, n=15). On admission, Glasgow Coma Score (GCS) of the bonsai with additional substance group was significantly higher (p=0,003). The most common symptom was palpitations (tachycardia) (75.5%, n=37). There were no patients hospitalized in Only Bonsai group (p=0,020). The median time to remission of symptoms and median follow-up time of the patients in the emergency room were 3 hours and 6 hours, respectively. Remission time of the symptoms and hospitalization rates were higher in patients with concomittant drug intake (p <0.05) Conclusion: While the bonsai intake alone is not considered mortal to the patients and most of them can be discharged from the ED after signs and symptoms disappear, concomitant drug use can increase the toxic effects of bonsai intake. That is why follow-up of patients taking concomitant drug and the treatment process should be carried out more carefully.